Do you have enough space? Habitat selection of insectivorous cave-dwelling bats in fragmented landscapes of Eastern Amazon. - Valéria da C Tavares; Mariane S Ribeiro; Xavier Prous; Alice A Notini; Nathalia Y Kaku-Oliveira; Leandro M D Maciel; Sérgio Sales; Juliana M Longo; Flávia M Evangelista; Lucas Rabelo; Iuri V Brandi; Santelmo S Vasconcelos; et al. (PLoS ONE)
Individual movements of bats are triggered by their life requirements, limited by their recognition of the environment and risks of moving, and mediated by habitat selection. Mining adds fragmentation and heterogeneity to landscapes, with poorly understood consequences to the life activities of the bats. Cave dwelling bats spend most of their life cycles within caves, and as they constantly forage in external landscapes, their contribution in the input of organic matter to the caves is of paramount importance to the subterranean biodiversity. We investigated habitat selection by cave bats in a mosaic of Amazonian forests, iron-rich savannas and iron-caves, studying the movements of the aerial insect-catcher Furipterus horrens (Furipteridae) and of the foliage gleaning bat Lonchorhina aurita (Phyllostomidae), both cave-dependent in the area. We used radio telemetry to assess their use of habitats, under the prediction that these species prefer preserved habitats for their foraging bouts, avoiding human-modified habitats. We also anticipated larger areas and commuting distances for both species when foraging in disturbed landscapes. Thirty-one bats were monitored in conserved habitats, mining sites and pastures resulting in an average range of 415.1 ± 837.4 ha and average commuting distances of 2163 ± 2453 m (F. horrens) and 681.1 ± 1101 ha and 2781.5 ± 2333 m (L. aurita). Our results suggest that F. horrens are open space foragers, frequently recorded in cangas, and L. aurita are forest foragers that use all habitats proportionally to their availability in the landscape. We detected landscape-related effects mediated by seasonal variation in the maximum commuting distance performed by both species. These are the first radiotelemetry data available for F. horrens and L. aurita, delivering original baselines to understand their movement behaviors. This information sheds light into constraints related to the optimal and adjusted biological cycles of these two species and their range shifts under scenarios of disturbance and may subsidize programs for their conservation.